Horvátország és Fiume a dualista korszak magyar nemzetpolitikai törekvéseiben - Makkai, Béla (Közép-Európai Közlemények, 2013)
In the summer of 1848 Croatia de facto succeeded from Hungary, and Ban Jelačić occupied Fiume. Giving up gave up three Slavonian counties for a sea entrance in Fiume, the Croatian-Hungarian Compromise of 1868 was regarded as the maximum of concessions by the Hungarian political elite, while the Croats viewed it as a promising beginning. The Croatian aspirations for the reorganization of the Habsburg Empire into a Trialist political system conflicted with the plans of Hungarians, who were mesmerized by Great Power status of the Danubian Empire. The victims of these political power plays became the 100.000 Hungarians living south to the River Drava in Slavonia. Budapest’s covert support policy, the Slavonian Action (1904–1920), chose these Slavonian Hungarians to be a barrier against Southern Slav aspirations and separatism. Meanwhile, for Hungary, Fiume became “a window for the world” and a “lighthouse” in the mourning Slavic sea. Should the Hungarian political elite have sacrificed Slavonian Hungarians for the sake of a lasting compromise with the Croats? Would it have been possible to maintain the co-entity status of Croatia and the equality of Croats in the Dualist Monarchy? This study seeks to give the answers for these questions.